Manajemen Pendidikan Karakter Cinta Tanah Air (Analisis Konseptual Peran Kepala Sekolah dan Guru) - Selamet B Hartanto (Wahana Islamika: Jurnal Studi Keislaman, 2019)
Nationalism as a character education is urgent to do because many Indonesian today do not understand the culture of the region itself, often refute school regulations, reduce social sense in Indonesian society, use impolite language, assume ceremonies and also reduce interest in manufactured products on own nation. This paper uses qualitative methods with literature study. Data analysis of this study uses data sourced from literature, whether in the form of books, magazines, journals, newspapers or other sources related to literature. The results of the analysis show that in the love management process of the homeland education, the principal has the most dominant task of managing management involving planning, organizing, coordinating, directing, and supervising. The teachers in the process of character education like land have an introductory agent so they are ready to accept assignments and responsibilities in the form of giving out material also related to examples that can be given to students.